2021
DOI: 10.3390/molecules26072000
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting the Ramifications of UVB Irradiation and Photoaging with Swietenia macrophylla King Seed

Abstract: In this day and age, the expectation of cosmetic products to effectively slow down skin photoaging is constantly increasing. However, the detrimental effects of UVB on the skin are not easy to tackle as UVB dysregulates a wide range of molecular changes on the cellular level. In our research, irradiated keratinocyte cells not only experienced a compromise in their redox system, but processes from RNA translation to protein synthesis and folding were also affected. Aside from this, proteins involved in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…Previously, there had been suggestions that the extract of S. macrophylla seeds had photoprotective properties. This can be seen in the research by Mahendra et al [61], where the seed extract displayed the ability to attenuate the damaging effect of UVB on human skin at a molecular level. Hence, although not reaching the critical value of 370 nm, photoprotective bioactive compounds might be present within the S. macrophylla seed extract and its fractions.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, there had been suggestions that the extract of S. macrophylla seeds had photoprotective properties. This can be seen in the research by Mahendra et al [61], where the seed extract displayed the ability to attenuate the damaging effect of UVB on human skin at a molecular level. Hence, although not reaching the critical value of 370 nm, photoprotective bioactive compounds might be present within the S. macrophylla seed extract and its fractions.…”
Section: Discussionmentioning
confidence: 90%
“…One well-known role of TIMP3 is the modulation of the inflammatory pathways via TNF-α through TNF-α-converting enzyme (ADAM17) [ 79 ]. As the production of TNF-α under UV exposure induces the release of cytokines, bringing about dermal inflammation and eventually collagen degradation, control of TIMP3 becomes essential in inhibiting photoaging [ 18 , 80 ]. Therefore, the decrease of both AQP3 and TIMP3 by UVB through core clock genes demonstrates the effect UVB has on the skin’s circadian rhythm and its induction of skin photoaging.…”
Section: Loss Of Circadian Rhythm Alongside Skin Elasticity and Colla...mentioning
confidence: 99%
“…In addition, other studies on proteins, such as Krüppel-like factor (KLF) 9 , peroxiredoxin 2, and sirtuin (SIRT) 3 and 4 , also showed that they all have rhythmic patterns in their expression in the human epidermal keratinocytes [ 86 , 87 , 88 ]. KLF9, a member of the KLF family, was suggested to affect cell proliferation and differentiation, while peroxiredoxins are antioxidant enzymes that are suppressed by UVB radiation [ 18 , 86 , 89 ]. As for SIRTs, they are ADP-ribosyltransferases and NAD (+)-dependent deacetylases that are involved in cell metabolism and epigenetics [ 87 ].…”
Section: Limitations and Research Gap In The Study Of Skin Circadian ...mentioning
confidence: 99%
See 2 more Smart Citations